Morphological characteristics and phylogenetic analyses reveal Purpureocorticium niveum sp. nov. (Agaricomycetes, Basidiomycota) from southern China - Yuan, Qi; You, Shichun; Zhou, Shili; Zhu, Yonggao; Li, Wen; Zhao, Changlin; Xu, Yongyan (Phytotaxa, 2025)
Purpureocorticium niveum sp. nov., discovered in Yunnan Province, southern China, is described here as a new species based on morphology and phylogenetic analyses. Purpureocorticium niveum is characterized by its cracking basidiomata with a smooth hymenial surface, a monomitic hyphal system with clamp connections on generative hyphae, and pyriform basidiospores. Phylogenetic analyses of the new species were conducted based on internal transcribed spacer (ITS) and large subunit (LSU) sequences. The phylogenetic analyses revealed that the new species belongs to the genus Purpureocorticium and was recovered as a sister species to P. microsporum. However, morphologically, P. microsporum differs from P. niveum by having pinkish purple basidiomata and relatively smaller basidiospores. A full description, illustrations, and phylogenetic analyses results of the new species are provided in this article.